Changes in erythrocyte membrane epoxyeicosatrienoic, dihydroxyeicosatrienoic, and hydroxyeicosatetraenoic acids during pregnancy - Somani, Selina T. (Life Sci, 2020)
AIMS: Pregnancy is associated with numerous changes in physiological and metabolic processes to ensure successful progression to full term. One such change is the alteration of arachidonic acid (AA) metabolism and formation of eicosanoids. This study explores the changes in AA metabolites formed through the cytochrome P450 mediated pathway to epoxyeicosatrienoic (EET), dihydroxyeicosatrienoic (DHET), and hydroxyeicosatetraenoic (HETE) acids which have been implicated in blood pressure regulation and inflammatory responses that are important for a healthy pregnancy. MAIN METHODS: The study determines circulating levels of EETs, DHETs and HETEs extracted from erythrocyte membranes and measured by mass spectroscopy during the progression of a normal pregnancy. Blood samples, from 25 women, were collected at three time points including 25-28 weeks gestation, 28-32 weeks gestation, and the non-pregnant control at 3-4 months postpartum. KEY FINDINGS: Results demonstrate that healthy pregnancy is associated with significant increases in 8,9-DHET, 11,12-DHET and 14,15-DHET and a decrease in trans 8,9-EET during 28-32 weeks gestation compared to 3-4 months postpartum. These differences are likely due to several mechanisms including an increase in soluble epoxide hydrolase activity, a decrease in glutathione conjugation, and altered cytochrome P450 enzyme expression and/or activity that occurs during pregnancy. SIGNIFICANCE: Metabolism of AA through the cytochrome P450 pathway generates physiologically important eicosanoids that could play an important role in the progression of a healthy pregnancy. Establishing the changes that occur during normal pregnancy may, in the future, help in early detection of pregnancy complications including pre-eclampsia.